Large ameloblastic fibro-odontoma in a 3 yearold child: case report - Laurindo Moacir Sassi; Roberta Targa Stramandinoli; José Luis Dissenha; Fernando Luis Zanferrari; Juliana Lucena Schussel (Revista Sul-Brasileira de Odontologia, 2012)
The ameloblastic fibro-odontoma is a rare mixed neoplasm composed of proliferating odontogenic epithelium, ectomesenchymal tissue, and varying degrees of dental hard tissue formation. The mean age of the incidence is from 8-12 years and there is no gender or anatomic site predilection, but it is most commonly found in children’s or teenager’s jaws. Case report: A 3-year-old female patient showed a swelling in anterior maxilla, with facial asymmetry. Radiographically, it presented as a mixed lesion with undefined limits. Clinical hypothesis was odontoma. Enucleating surgery was conducted with tooth germs preservation. The final diagnosis was ameloblastic fibro-odontoma. No recurrence was observed at 1-year follow-up period, and the permanent tooth germs were correctly positioned for eruption. Conclusion: Although ameloblastic fibro-odontoma is a benign lesion, it developed in a very early age, with rapid growth and destruction of cortical bone. Proper surgical enucleation allowed the teeth maintenance.